Peptidyl ω-Asp Selenoesters Enable Efficient Synthesis of N-Linked Glycopeptides - Du, Jing-Jing; Zhang, Lian; Gao, Xiao-Fei; Sun, Hui; Guo, Jun (Frontiers in Chemistry, 2020)
Chemical synthesis is an attractive approach allows for the assembly of homogeneous complex N-linked glycopeptides and glycoproteins, but the limited coupling efficiency between glycans and peptides hampered the synthesis and research in the related field. Herein we developed an alternative glycosylation to construct N-linked glycopeptide via efficient selenoester-assisted aminolysis, which employs the peptidyl ω‑asparagine selenoester and unprotected glycosylamine to perform rapid amide-bond ligation. This glycosylation strategy is highly compatible with the free carboxylic acids and hydroxyl groups of peptides and carbohydrates, and readily available for the assembly of structure-defined homogeneous N-linked glycopeptides, such as segments derived from glycoprotein EPO and IL-5.